Green Solver Card Game: Needs Analysis and Design for Green Chemistry Learning - Rahma, Siregar Aliya; Watulingas, Maasje Catherine; Nurhadi, Mukhamad (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This research is driven by the instructional saturation and passive learning environment observed in green chemistry education at SMAN 8 Samarinda. The study aims to conduct a needs analysis and design an interactive learning medium called the Green Solver card game to increase student engagement and conceptual understanding. Using the Research and Development (R&D) approach with the ADDIE model, this research is specifically limited to the analysis and design stages. The subjects involved in this preliminary study were 1 chemistry teacher and 189 tenth-grade students as the primary data sources. The analysis stage, conducted through interviews and questionnaires, revealed that 76.2% of students found existing static media uninteresting, while 92.1% expressed a strong preference for the integration of game-based learning. In the design stage, the Green Solver card game was developed by adapting the "Truth or Dare" social mechanism into two strategic components: Theory cards and Action cards. Theory cards serve as retrieval practice tools to strengthen conceptual memory, whereas Action cards incorporate gamified challenges and environmental problem-solving tasks to alleviate learning anxiety and promote social collaboration. The resulting design includes a comprehensive guidebook, a tiered scoring system (5-40 points), and visual elements optimized for cognitive processing through dual coding. This study successfully produced a prototype blueprint that offers a holistic solution to transform classroom dynamics from passive to active learning.